2019
DOI: 10.1016/j.ffa.2018.12.006
|View full text |Cite
|
Sign up to set email alerts
|

The subfield codes of hyperoval and conic codes

Abstract: Hyperovals in PG(2, GF(q)) with even q are maximal arcs and an interesting research topic in finite geometries and combinatorics. Hyperovals in PG(2, GF(q)) are equivalent to [q + 2, 3, q] MDS codes over GF(q), called hyperoval codes, in the sense that one can be constructed from the other. Ovals in PG(2, GF(q)) for odd q are equivalent to [q + 1, 3, q − 1] MDS codes over GF(q), which are called oval codes. In this paper, we investigate the binary subfield codes of two families of hyperoval codes and the p-ary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 15 publications
2
38
0
Order By: Relevance
“…One of the important questions for a code with parameters and , is: how many nonisomorphic codes are there having these parameters? Many researches discussed this question directly by working on the code, see for example [7,8], or indirectly through projective space, both in general cases and for a certain , see for example [9,10,11]. The first objective of this paper is to present a class of non-isomorphic error-correcting -MDS codes over of two and three dimensions with their weight distributions.…”
Section: {∑ / ( ) }mentioning
confidence: 99%
See 1 more Smart Citation
“…One of the important questions for a code with parameters and , is: how many nonisomorphic codes are there having these parameters? Many researches discussed this question directly by working on the code, see for example [7,8], or indirectly through projective space, both in general cases and for a certain , see for example [9,10,11]. The first objective of this paper is to present a class of non-isomorphic error-correcting -MDS codes over of two and three dimensions with their weight distributions.…”
Section: {∑ / ( ) }mentioning
confidence: 99%
“…Therefore, the Hamming weight of this code is 1. Over the field , the Hamming weights of vectors in the generating matrix take the values 1, 2, 3,4,5,6,7,8,9,10,11,12,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,…”
Section: Al-zangana and Shehabmentioning
confidence: 99%
“…By definition, the dimension k ′ of C (q) satisfies k ′ ≤ mk. To the best of our knowledge, the only references on subfield codes are [4], [5], [11], [14]. Recently, some basic results about subfield codes were derived and the subfield codes of ovoid codes were studied in [11].…”
Section: B Subfield Codesmentioning
confidence: 99%
“…It was demonstrated that the subfield codes of ovoid codes are very attractive [11]. The parameters of some hyperoval codes and the conic codes were also studied in [14].…”
Section: B Subfield Codesmentioning
confidence: 99%
“…, A n ) is an important research object in coding theory, as it contains crucial information about the error correcting capability of the code. Thus study on weight distribution of linear codes attracts much attention in coding theory and many works focus on determining weight distribution of linear codes (see, for example, [6,7,8,9,10,11,15,21,22,23,24] and the references therein). A code C is said to be a t-weight code if the number of nonzero A i in the sequence (A 1 , A 2 , • • • , A n ) is equal to t. Denote by C ⊥ the dual code of a linear code C. We call an [n, k, d] code distance-optimal if no [n, k, d + 1] code exists and dimensionoptimal if no [n, k + 1, d] code exists.…”
Section: Introductionmentioning
confidence: 99%